Populizem in identitetna politika proti globalizaciji in neoliberalizmu - Adam, Frane (Teorija in praksa, 2017)
The text deals with the recent outbursts of populism seen in both the USA and Europe. The thesis is that populism is a reaction to the anomalies and unintended consequences of globalisation. By considering three models of social development, we show that populist leaders are accentuating the loss of national sovereignty, the dominance of supranational institutions (including the EU), as well as the penetration of big capital and multinational corporations. It is important that the EU takes on a more active role in regulating free trade, the flow of capital, and migrations by combining openness and the autocentric model. Should this not occur, the populists will tend to prefer more closed national systems.
Keywords: Democracy; Demokracija; Globalizacija; Globalization; Nacionalizem; Nationalism; Neoliberalism; Neoliberalizem; Populism; Populizem